Morphine in acute heart failure - Agewall, Stefan (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Acute pulmonary oedema is a common condition in the emergency room, associated with considerable mortality. Morphine has since a long time, been used in patients with acute pulmonary oedema due to its anticipated anxiolytic and vasodilatory properties; however a discussion about the benefits and risks has been raised recently (1). There are no large randomised controlled trials supporting the use of morphine in the treatment of patients with acute heart failure (AHF). A certain vasodilation has been described after morphine administration (2), but the evidence for this mechanism is relatively poor and morphine-induced anxiolysis may possibly be the most important factor of morphine in pulmonary oedema and therefore some authors have suggested benzodiazepines as an alternative treatment (3).